The effects of ischemic preconditioning on skeletal muscle deoxygenation during an exhaustive cycling test - Jenner, W. J.; Gyori, A.; Fallan, C.; Cunniffe, B.; Montgomery, H. E.; MacAllister, R. J.; Cardinale, M. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Ischemic preconditioning (IPC) is a physiological phenomenon whereby non-lethal intermittent ischemia induces protection against lethal ischemic episodes. IPC also improves tolerance to intense exercise resulting in improved power output and increased VO2 max (de Groot et al. 2010). Based on the potential of IPC to modulate blood vessel and skeletal muscle function, we aimed to study whether IPC improves muscle oxygenation during incremental exercise in well-trained individuals. Methods: Thirteen well-trained male club cyclists (aged 33±6 years, height 180±6cm, weight 78.5±4.0kg, [mean±s.d.]) were randomised to IPC or sham IPC using a crossover design. IPC was induced using three 5-minute cycles of inflation and deflation of a blood pressure cuff on the thighs to suprasystolic blood pressure. Sham IPC was induced using a subdiastolic cuff pressure, and the crossover interval was 7 days. The inflations were followed by an incremental exercise test on a cycle ergometer; 4 minutes of warm-up at 150W followed by 50W/min increases at a constant cadence until exhaustion. Muscle oxygenation was assessed in-vivo by means of near-infrared spectroscopy (NIRS - InSpectraTM 650, Hutchinson Technology). From the NIRS signal, the ratio of oxygenated haemoglobin to total haemoglobin in the microcirculation was calculated and used for analysis (StO2). Repeated measures ANOVA was used to analyse the data (P<0.05 deemed significant). Results: IPC reduced StO2 to a higher degree than sham during cuff inflations (P=0.001). StO2 was significantly reduced during exercise in both treatment groups (P<0.0001). There was a trend for IPC to preserve muscle oxygenation during exercise compared with the sham intervention, which was observed in 11 of the 13 subjects (P=0.07). Discussion: The IPC protocol employed in this study was effective in producing ischemia and reperfusion in the vastus lateralis muscle. Despite not reaching statistical significance, IPC showed potential to ameliorate the reduction in StO2 during exercise in an incremental cycle ergometry exercise compared with sham. Whether IPC improves oxygen delivery to skeletal muscle or increases metabolic efficiency remains to be determined. Further work aims to identify whether IPC can influence additional outcomes of sporting performance.